2003
DOI: 10.1245/aso.2003.03.015
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram for Predicting the Likelihood of Additional Nodal Metastases in Breast Cancer Patients With a Positive Sentinel Node Biopsy

Abstract: We have developed a user-friendly nomogram that uses information commonly available to the surgeon to easily and accurately calculate the likelihood of having additional, non-SLN metastases for an individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
509
7
40

Year Published

2009
2009
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 753 publications
(580 citation statements)
references
References 38 publications
22
509
7
40
Order By: Relevance
“…No model, including the nomogram of Van Zee, is ideal for providing an estimate of the likelihood of finding additional disease in non-SLNs [6]. However, the size of the SLN is significantly predictive of additional non-SLN metastases and size measurement is therefore essential for staging and management of breast cancer patients [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No model, including the nomogram of Van Zee, is ideal for providing an estimate of the likelihood of finding additional disease in non-SLNs [6]. However, the size of the SLN is significantly predictive of additional non-SLN metastases and size measurement is therefore essential for staging and management of breast cancer patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations found that the size of the SLN metastasis is significantly predictive of the likelihood of additional, non-SLN metastases [6]. The AJCC Cancer Staging Manual, 6 th edition includes size of the metastasis as a determining factor of stage and therefore of prognosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…The probability of additional non-SLN metastasis was calculated using the MSKCC nomogram developed by Van Zee et al for patients with complete pathologic information who fit the nomogram inclusion criteria. 3 Among the 302 patients who received RT, 174 received RT at MSKCC, and 128 received RT at outside institutions. RT volumes were classified as standard tangents, high tangents, comprehensive, or partial breast.…”
Section: Methodsmentioning
confidence: 99%
“…Methods of enhanced pathologic assessment of the SLN node have resulted in the increased detection of small-volume (micrometastases and isolated tumor cells) SLN metastases. 1,2 Nomograms that identify patients at low risk for additional lymph node metastases have guided the selection of patients for SLNB alone, 3 leading to a nationwide decline in the performance of completion axillary dissection (cALND). 1 These trends are reflected at our own institution, where cALND rates between 1998 to 2008 decreased from 85% to 73%.…”
Section: Introductionmentioning
confidence: 99%
“…The nomogram from the Sloan-Kettering Cancer Center [2] is based on eight variables: tumour size, type and grade, lymphovascular invasion, multifocality, oestrogen receptor status, method of sentinel lymph node metastasis detection, number of positive sentinel lymph nodes and number of negative sentinel lymph nodes. The other three scores are simpler than this and they use only three parameters.…”
mentioning
confidence: 99%